Bovine respiratory disease-associated ultrasonographic lung lesions in Holstein calves: a genomic perspective on copy number variants and homozygosity - Bernini, Francesca; Boccardo, Antonio; Delledonne, Andrea; Bronzo, Valerio; Lanfredi, Giacomo; Bagnato, Alessandro; Strillacci, Maria G. (Frontiers in Animal Science, 2025)
Bovine respiratory disease (BRD) poses a significant health and economic challenge in cattle farming, particularly affecting young calves. Although previous SNP-based genome-wide association studies (GWAS) have identified candidate loci linked to BRD susceptibility, they only explain a fraction of the trait’s heritability. Using genotypes from a previous study that employed a selective genotyping approach, we analyzed Holstein calves classified as BRD-resistant or BRD-susceptible, based on thoracic ultrasonography and clinical scoring. In particular, structural variations, specifically copy number variants (CNVs) and runs of homozygosity (ROH), were investigated due to their emerging role as complementary genomic features that may be involved in disease resistance. A total of 2,666 CNVs were identified, and the CNV-GWAS revealed 10 significant CNV regions (CNVRs), encompassing or near 15 candidate genes. While the ROH analysis identified 8,226 segments, we further applied a fixed-window approach to compare ROH frequencies between groups, revealing 19 regions with significantly different ROH frequencies. Gene annotation of both CNVRs and differential ROH windows uncovered genes linked to immune response, lung development, and known BRD-associated pathways. Functional enrichment analyses using DAVID and Cytoscape-GeneMANIA indicated involvement of antiviral responses, GPCR signaling, calcium signaling, and estrogen receptor pathway in disease resistance. Notably, 37% of the genes identified in this study overlapped with those reported in previous BRD-related studies. This integrative genomic analysis highlights the relevance of structural variation in shaping BRD resistance and susceptibility in dairy calves. By integrating CNV mapping, ROH analysis, and functional annotation approaches, we identified novel and previously reported candidate genes potentially involved in innate immune processes. These findings support the implementation of precision breeding strategies aimed at improving disease resilience in cattle.